2006
DOI: 10.1111/j.1529-8817.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

A MULTI‐GENE MOLECULAR INVESTIGATION OF THE KELP (LAMINARIALES, PHAEOPHYCEAE) SUPPORTS SUBSTANTIAL TAXONOMIC RE‐ORGANIZATION1

Abstract: Every year numerous ecological, biochemical, and physiological studies are performed using members of the order Laminariales. Despite the fact that kelp are some of the most intensely studied macroalgae in the world, there is significant debate over the classification within and among the three ''derived'' families, the Alariaceae, Laminariaceae, and Lessoniaceae (ALL). Molecular phylogenies published for the ALL families have generated hypotheses strongly at odds with the current morphological taxonomy; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
331
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(355 citation statements)
references
References 74 publications
(129 reference statements)
12
331
1
1
Order By: Relevance
“…The few exceptions were generally concordant with the current phylogenies (Yoon et al, 2001;Lane et al, 2006). For example, two loci (rps14/atp8 and rpl31/rns) amplify in only one of the two Lessoniaceae species of the tested taxa, Ln and Mp, but both Yoon et al, (2001) and Lane et al, (2006) demonstrated that these are paraphyletic.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The few exceptions were generally concordant with the current phylogenies (Yoon et al, 2001;Lane et al, 2006). For example, two loci (rps14/atp8 and rpl31/rns) amplify in only one of the two Lessoniaceae species of the tested taxa, Ln and Mp, but both Yoon et al, (2001) and Lane et al, (2006) demonstrated that these are paraphyletic.…”
Section: Discussionmentioning
confidence: 50%
“…In the Phaeophyceae, the existing repertoire of mitochondrial markers has generally been limited to conserved coding regions used for higher-order phylogenetics (Ehara et al, 1999;Lane et al, 2006;Oudot-Le Secq et al, 2006), detection of interspecific hybridization (Coyer et al, 2002a,b) and, more recently, for phylogeographic studies (Muraoka & Saitoh, 2005;Uwai et al, 2006a). However, for lower-level taxonomic and population-level studies, presumably neutral, non-coding regions, such as introns or intergenic spacers are preferable, to avoid the confounding effects of selection, which are particularly problematic in phylogeographic studies where patterns of gene flow must be inferred from gene genealogies.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses showed that 'Ailunwan' firstly groups with Saccharina japonica. It indicated that 'Ailunwan' had a closer evolutionary relationship with Saccharina than Laminaria, supporting current taxonomic systems (Yoon et al 2001;Lane et al 2006). …”
mentioning
confidence: 54%
“…Second, east-west differences in deep-water tropical kelp genera are conspicuous. The eastern tropical Pacific contains Eisenia only, one of the most derived genera in the kelp order Laminariales (21). The western tropical Pacific and Atlantic Oceans harbor three species of deep-water Laminaria, all of which have primitive traits for the Laminariales (16,17), suggesting an ancient origin (Ͼ30 Mya) (22) and relative permanence of deep-water kelp refugia.…”
mentioning
confidence: 99%